TRIANGULATING SOME DISCOURSE-RELATED ISSUES IN INDONESIAN EFL PRE-SERVICE TEACHERSÃ¢â¬â¢ WRITTEN NARRATIVES - Joseph Ernest Mambu (TEFLIN Journal: A publication on the teaching and learning of English, 2009)
Abstract: This paper attempts to document how the notion of discourse was made sense of by EFL teachers from the U.S.A. and by me as an Indonesian who read and commented on 16 narratives written by four male and four female pre-service/student teachers. While the Americans tended to focus on the superficial content and textual organizations, I have found it crucial to appreciate the themes, styles, and philosophies these pre-service teachers presented in their narratives. First, the themes were clustered, thus showing how one pedagogical story relates to or differs from another. Second, the styles of arranging thoughts indicate how Indonesian teachers in this study were overall more indirect so the American readers assumed more responsibility to decipher their implied meanings. From my perspective, however, the salient discourse style is that of philosophizing. In essence, the philosophies in several narratives reflect traces of the ongoing process of believing what these teachers did or practiced as prospective teachers or as colleagues.